Concurrent validity of an easy-to-use inertial measurement unit-system to evaluate sagittal plane segment kinematics during overground sprinting at different speeds - de Ruiter, C. J., Wilmes, E.; Brouwers, S. A. J.; Jagers, E. C.; van Dieën, J. H. (Sports Biomechanics, 2022)
This study investigated concurrent validity of inertial measurement units (IMUs) and high-speed video for sagittal plane kinematics during overground sprinting. The practical relevance is demonstrated by reporting the changes in thigh kinematics in relation to toe-off and touch-down of the feet at near maximal to maximal (80-100%) speeds. Sixteen athletes ran multiple 60 m sprints with IMUs on their feet, shanks, thighs, pelvis and trunk. High-speed video data were captured of the start strides and of one complete stride at full speed. Coefficients of multiple correlation with video were >0.99 for angles and angular velocities of the thigh and shank but low for the pelvis and trunk (0.13-0.66). For the limb segment angles (minimum, maximum, at toe-off and at touch-down) absolute biases (limits of agreement) were =2.9°(=7.7°) and for angular velocities the values were =57°.s-1(=93°.s-1). Many of the expected speed-related changes in thigh kinematics were significant (linear mixed effect regression; p < 0.05).